Batasan Waktu Pelaksanaan Salat Jenazah di Area Pemakaman dalam Perspektif Fikih Ibadah: Time Limit for Performing Funeral Prayers in Funeral Areas from the Perspective of the Jurisprudence of Worship - Fadhlan Akbar; Chamdar Nur; M. Fadil Azhabul Izza (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to explore and understand scholars' views on the law and time limits for performing funeral prayers at burial sites within the perspective of fiqh (Islamic jurisprudence) on worship practices. This qualitative descriptive research (non-statistical), using normative and historical approaches. The findings of the study are as follows. First, scholars differ in their opinions regarding the ruling on funeral prayers at the burial site for those who missed the initial prayer. The first opinion, held by the Hanafi school, permits it with conditions: the person must be a guardian of the deceased and the initial funeral prayer must not have been led by another guardian; the person must have the right to perform the prayer for the deceased. The second opinion, from the Maliki school, considers it disliked (makruh) to repeat the funeral prayer if it was already conducted collectively, but it is permitted if only one person prayed earlier, provided it is done in congregation. The third opinion, from the Shafi’i and Hanbali schools, allows it unconditionally. The researcher tends to favor the third opinion. Second, there are five opinions regarding the time limit for funeral prayers at the burial site: (1) limited to three days, which is a view held by some Hanafi scholars; (2) up to one month, supported by some scholars from the Hanbali, Maliki, and Shafi’i schools; (3) as long as the body remains intact, a view held by some Hanafi, Maliki, and Shafi’i scholars; (4) allowed indefinitely without restriction, a position taken by some Shafi’i scholars and Ibn 'Aqil al-Hanbali; and (5) allowed indefinitely with the condition that the person met the requirements to pray at the time of the deceased’s passing, which is a Shafi’i view. The researcher favors the fifth opinion. The implications of this study are intended to serve as a resource for students of knowledge and to provide information for the public seeking insight into this topic.